The comparative analysis of the industrial relations systems in Europe - Juliusz Gardawski; Rafał Towalski (International Journal of Management and Economics, 2020)
This article aims to quantify the institutional similarities between industrial relations systems in 11 Central and Eastern European countries (CEE11), on the one hand and each of the four models of capitalism in Western Europe identified by Amable [2003], on the other hand. The comparative analysis was performed on the basis of six variables. Three of them represent inputs or institutional determinants of industrial relations. Another three variables represent outputs or the labor market performance. For each variable, the similarity coefficients between CEE11 countries and four reference EU15 economies representing Western European models of capitalism were calculated. Based on these coefficients, the hexagons of similarity were built. The analyses led us to some general observations. In 2005, most of the countries in the region developed industrial relations systems similar to the continental model, what can be interpreted as a strategy to meet the requirements imposed on these countries in the process of European integration. After accession, most of the countries abandoned "social partnership" ship and started the cruises to the Anglo-Saxon model.
Keywords: J5; P16; P51; 650; industrial relations system; Central and Eastern Europe; capitalism models; comparative studies